Beets beyond sugar: potential and limitations of sugar beet pulp as a feedstock for biorefineries - Dhodduraj, Kawinharsun; Narisetty, Vivek; Nabavi, Seyed Ali; Parra-Saldívar, Roberto; Coulon, Frederic; Agrawal, Deepti; Maity, Sunil K.; Balan, Venkatesh; Kumar, Vinod (Elsevier, 2026)
Sugar beet (SB) is a major sugar crop in the European Union and the United States, primarily cultivated for the commercial production of table sugar. Post-extraction of sucrose, the fibrous fraction which remains is called sugar beet pulp (SBP). SBP is rich in structural carbohydrates such as cellulose, hemicellulose and pectin containing glucose, arabinose and galactouronic acid as their respective monomeric units. SBP is a renewable source of fermentable sugars that constitute about 85 % of total carbohydrates. Leveraging SBP as a substrate for a biorefinery supports circular bioeconomy principles by simultaneously reducing agricultural waste and enabling the sustainable production of value-added chemicals. This review highlights current advances in SBP valorization, beginning with an overview of SB processing and waste generation, followed by a critical assessment of pretreatment strategies that enhance carbohydrate accessibility. Particular attention is given to emerging routes for the bioconversion of arabinose and galacturonic acid, which together represent more than half of SBP’s fermentable fraction yet remain significantly underutilized in industrial biotechnology. Microbial pathways, metabolic engineering interventions, and fermentation approaches enabling the production of value-added compounds such as arabitol, 2,3-butanediol, ascorbic acid, mucic acid and prebiotics are examined in detail. The review concludes by addressing current challenges and identifying research gaps to unlock the full potential of SBP within integrated biorefinery systems.
Keywords: Biotechnology; 3004 Crop and pasture production; 3006 Food sciences; 4004 Chemical engineering; Sugar beet pulp; Biorefinery; Pretreatment; Arabinose; Galacturonic acid; Fermentative bioconversion